Venous thromboembolism and its prophylaxis in elective knee arthroplasty: an international perspective. - Khokhar, A; Chari, A; Murray, D; McNally, M; Pandit, H (2013)
INTRODUCTION: Patients undergoing knee arthroplasty are at high risk of developing post-operative deep vein thrombosis (DVT) or a pulmonary embolus (PE). Despite best efforts, the best prophylaxis for thromboembolic disease remains controversial. This article aims to update the reader on the newest guidelines concerning venous thromboembolism (VTE) prophylaxis for elective knee arthroplasty, highlighting their inconsistencies and why variations in recommendations exist. METHODS: The Medline database and the Internet were searched for VTE prophylaxis guidelines in English. 12 guidelines were found and compared. The comparison looked at the recommendations made, the grade of recommendation, the level of evidence available for these recommendations and any inconsistencies between the guidelines. RESULTS: Nearly all the guidelines advocate the use of low molecular weight heparin (LMWH) and Fondaparinux. There is little consensus in terms of other recommended drugs, the doses, duration and their recommendation grades. There are marked differences in the methodologies adopted by the different guideline working-groups. CONCLUSION: There is still uncertainty about the optimal methods of thromboprophylaxis in elective knee arthroplasty. Although there are always going to be disagreements about the endpoints amongst guideline makers, guidelines should achieve uniformity in their reporting of end-points, criteria for levels of evidence and recommendation grades, facilitating the clinician's decision-making process.